Specific characteristics of hemorrhagic Meckel’s diverticulum at double-balloon endoscopy - Mizutani, Yasuyuki; Nakamura, Masanao; Watanabe, Osamu; Yamamura, Takeshi; Funasaka, Kohei; Ohno, Eizaburo; Kawashima, Hiroki; Miyahara, Ryoji; Murino, Alberto; Goto, Hidemi, Professor; Hirooka, Yoshiki (Endoscopy International Open, 2017)
Background and study aims Diagnosis of Meckel’s diverticulum (MD) before surgery may be challenging; double-balloon endoscopy (DBE) facilitates identification of MD in the setting of a gastrointestinal bleeding; however, MD can be found incidentally without this condition. The purpose of this research was to determine specific characteristic of hemorrhagic MD and incidental MD at DBE.Patients and methods Ectopic gastric mucosa enclosed in the MD and/or ulceration were defined as “major findings”; ring-like scar surrounding the MD was defined as “minor finding”. We retrospectively reviewed the medical records of patients affected by MD and analyzed the findings that significantly affected the characterization of MD.Results MD was diagnosed in 33 patients. The axis of the diverticulum was longer in hemorrhagic MD compared to incidental MD (P = 0.031). The amount of transfusion was significantly higher (P = 0.018) in the hemorrhagic MD group. Hemorrhagic MD was significantly more correlated with major findings (P = 0.01) and minor findings (P < 0.01). The specificity of major finding was 100 % while the sensitivity of major and/or minor findings was 96 %.Conclusions The combination of major and minor findings appears to improve the diagnostic ability of hemorrhagic MD avoiding unnecessary diverticulectomy.